The Effect of Autologous Serum Eye Drop Application on Epithelization in the Treatment of Various Ocular Surface Disorders and its Safety - Fatma Selin Kaya; Yonca Aydın Akova (Türk Oftalmoloji Dergisi, 2012)
Pur po se: To evaluate the effect of autologous serum application on epithelization in the treatment of ocular surface disorders in hard cases and its safety. Ma te ri al and Met hod: Patients with serious ocular surface disorders, unresponsive to conventional treatment were recruited. Clinical features of retrospective cohort of patients who were prescribed serum drops are presented. From July 2007 to January 2010, 31 eyes of 21 patients, who were given autologous serum eye drops, were included into the study. Clinical examination included epithelial changes, rose bengal/lissamine green staining, fluorescein staining, and tear film break-up time. A history of systemic disease was recorded together with systemic medications used. A complete ocular history was also obtained. Re sults: Autologous serum was used in 7 patients with delayed epithelization after penetrating keratoplasty, in 4 patients with epithelial disturbances secondary to keratitis, in 2 patients with alkali burns, in 3 patients with Stevens-Johnson syndrome, in 1 patient with ligneous conjunctivitis, in 1 patient with epidermolysis bullosa, in 1 patient with corneal burn with hot water, and in 2 patients with Sjogren syndrome. The female:male ratio was 13:8. The mean age was 36.23±24.80 standard deviation (range: 7 months-87 years). No significant sight-threatening complication has been observed with the use of serum drops. Dis cus si on: Autologous serum application is safe and efficient additional therapy in the treatment of serious ocular surface problems in difficult cases. (Turk J Ophthalmol 2012; 42: 336-41)